2020
DOI: 10.34172/apb.2021.057
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Phytofabricated ZnO and CuO NPs by Mentha pulegium Leaf/flower Mixture Extract against Antibiotic Resistant Bacteria

Abstract: Purpose: In this study, leaf/flower aqueous extract of medicinal plant species Mentha pulegium was used to synthesize ZnO and CuO nanoparticles (NPs) as a cost-effective, one-step, and eco-friendly method. Methods: Physicochemical properties of both metal oxide NPs (MONPs) were determined by UV-Vis spectroscopy, X-Ray Diffraction (XRD), Fourier-Transform Infra-Red (FTIR) spectroscopy, Scanning Electron Microscope (SEM) and Energy Dispersive X-ray (EDX) techniques. Results: Phytofabricated ZnONPs and CuNPs ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…For instance, the intensity of the approximately 1576 cm −1 peak in the CV spectrum decreased after the reaction, and the peak shifted to approximately 1564 cm −1 . Upon closer inspection, the precipitate spectra were found to contain a weak peak at approximately 1124 cm −1 corresponding to C-O stretching in the tertiary alcohol, which is not present in the CV structure [ 24 ]. Compared with the spectrum of SV9, the spectra of the precipitates clearly show that the peak positions and intensities are well matched.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the intensity of the approximately 1576 cm −1 peak in the CV spectrum decreased after the reaction, and the peak shifted to approximately 1564 cm −1 . Upon closer inspection, the precipitate spectra were found to contain a weak peak at approximately 1124 cm −1 corresponding to C-O stretching in the tertiary alcohol, which is not present in the CV structure [ 24 ]. Compared with the spectrum of SV9, the spectra of the precipitates clearly show that the peak positions and intensities are well matched.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR results demonstrated that the band in the wavenumber range of 3400–3000 cm −1 was associated with the stretching vibrations of the O–H groups of water molecules, as well as those of the phenolic and alcoholic compounds of the essential oil like menthol (Alavi et al., 2021 ). The peak at 2968.83 cm −1 was ascribed to the asymmetric stretch of C–H and CH 3 groups (Petrakis et al., 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial resistance often occurs as a result of the treatment of infectious diseases by misuse of antibiotics and is a global problem that affects the environment, human and animal health, as well as agriculture and the economy [5,6]. Bacterial resistance to antibiotics can be either innate or acquired [7]. Meanwhile, antibiotic resistance has become a global problem among the clinical strains of Acinetobacter, Klebsiella, Pseudomonas aeruginosa, Proteus, Escherichia coli, and Enterobacter species, and becomes a concern when this resistance can be transmitted through motile genetic elements (MGE) [8].…”
Section: Introductionmentioning
confidence: 99%